Spatial Practices Medieval/Modern (Volume 6) - Stock, Markus; Vöhringer, Nicola (2014)
This collection of essays approaches the study of space and place from a historically inclusive perspective; it gives new insights into historical shifts and changes in the construction and perception of space as well as historical developments and diachonicity of literary, social, and architectural sites and places. It aims to gather a number of case studies in order to collect historically concrete evidence of such spatial practices as reflected in literature and art as well as in sources pertaining to the social and political life of premodern, early modern, and modern era.